2013
DOI: 10.1177/0141076812472620
|View full text |Cite
|
Sign up to set email alerts
|

Mobile health use in low- and high-income countries: an overview of the peer-reviewed literature

Abstract: The evolution of mobile phone technology has introduced new possibilities to the field of medicine. Combining technological advances with medical expertise has led to the use of mobile phones in all healthcare areas including diagnostics, telemedicine, research, reference libraries and interventions. This article provides an overview of the peer-reviewed literature, published between 1 August 2006 and 1 August 2011, for the application of mobile/cell phones (from basic text-messaging systems to smartphones) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
151
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 222 publications
(151 citation statements)
references
References 52 publications
0
151
0
Order By: Relevance
“…26 Such is the appeal of this technologically rich resource that in 2013 it was reported that 65% of US adults owned a smartphone. 27 Medical professionals are certainly no exception with it being reported as early as 2010 that 80% of medical doctors in the UK owned a smartphone.…”
Section: Smartphone Prevalencementioning
confidence: 99%
“…26 Such is the appeal of this technologically rich resource that in 2013 it was reported that 65% of US adults owned a smartphone. 27 Medical professionals are certainly no exception with it being reported as early as 2010 that 80% of medical doctors in the UK owned a smartphone.…”
Section: Smartphone Prevalencementioning
confidence: 99%
“…Evidence shows that mobile health market has a year-over-year growth rate of around 17% since 2010 [11]. This growth has happened in all health-care areas including diagnostics, telemedicine, research, education, and interventions [12]. In fact, scope of mHealth applications has been expanded [13].…”
Section: Discussionmentioning
confidence: 99%
“…Several scientific papers show that short message service (SMS) based mHealth intervention have the potential to improve maternal and child health [13][14][15][16][17][18]. SMS based mHealth messaging provides an important role for maternal health care like reminders for healthcare appointments [19].…”
Section: According To Edhs 2016 Key Indicators Report Maternal Mortalmentioning
confidence: 99%